Knowledge building in the social Web: state of the art (2016)
This paper presents the state of the art on meanings and knowledge construction through the social web. It is the result of a doctoral research aiming to develop a descriptive and comprehensive model of the relationships, movements, and actions involved in knowledge production in the social web. To make them visible, the research was focused on traveler knowledge. A search on meta search engines and specialized journals was conducted. First a preselection of articles took place, followed by choosing articles which permitted to review, in detail, texts from researchers conducted in Asia (including Australia and New Zealand), Europe, Latin America and North America. A recently created area of knowledge, with a high rate of change, was found. Another finding was that it is still not possible to understand the motivational logic leading people to the creation or maintenance of collaboration based projects. Finally, the meanings assigned to traveler knowledge in the social web are related to ways of expression, identity and (social) relationships.